Comparison of Ki67 index and P16 expression in different grades of cervical squamous intraepithelial lesions - Maryam Sadat Hosseini; Maryam Talayeh; Noushin Afshar Moghaddam; Maliheh Arab; Farah Farzaneh; Tahereh Ashrafganjoei (Caspian Journal of Internal Medicine, 2023)
Background: the assessment of P16 expression and Ki-67 proliferative index is now proposed as an adjunct test for the diagnosis of high-risk precursor lesions for cervical cancer. The aim of the present study was to elucidate the quality expression of P16 and quantification Ki-67 index in different types of cervical intraepithelial neoplasia and also to determine the cutoff for Ki67 index to predict the severity of CIN lesions. Methods: This cross-sectional study was conducted on patients with colposcopic indication. Selected samples with different CIN grades were examined for P16 and Ki-67 index by immunohistochemical (IHC) methods. Results: All LSIL (CIN I) cases were negative for P16, while in 58.7% of HSIL cases (CIN 2/3), P16 was positive. The mean Ki67 index in the present study was 3.13 ± 2.65 in the upper two/third of the squamous epithelium in the LSIL group and 19.04 ±36.40 in the HSIL group, which was statistically significant. Also, the mean Ki67 index in full thickness squamous epithelium in HSIL group was significantly higher than LSIL. The sensitivity of P16 and Ki67 index in our study was 58.73%, 66.67% and the specificity was 100% and 100%, respectively. Conclusion: Assessment of P16 expression and Ki67 index can be used to distinguish low grade (CIN1) intraepithelial lesion from high grade (CIN2/3) intraepithelial or precancerous lesions.